2012
DOI: 10.33899/rden.2012.65095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Time on the Degree of Conversion of Light Cured Dental Materials

Abstract: Nayif A Jado EngineerABSTRUCT Aims: The aim of this study was to investigate the effect of storage time (immediately after polymerization and after one month of artificial saliva storage) on the degree of conversion (DC) of restorative type of light cured dental materials. Materials and Methods: Sixty samples of polyethylene molds were prepared. The samples were divided into three groups each of 20. The first group was filled with Composite resin, second group was filled with Compomer and the third group was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This is due to the fact that the polymerization process in light-activated composites continues for some time after the light source has been removed, and the DC exhibited a progressive rise following light exposure and storage in saliva. 57 This outcome, which was in agreement with Gahse et al 58 who demonstrated that a resin composite conversion rate with water storage rose considerably after one month. The current study may not accurately represent the oral environment because it was an in vitro investigation with a limited sample size.…”
Section: Table 5: Degree Of Conversion Mean Value (%)supporting
confidence: 90%
“…This is due to the fact that the polymerization process in light-activated composites continues for some time after the light source has been removed, and the DC exhibited a progressive rise following light exposure and storage in saliva. 57 This outcome, which was in agreement with Gahse et al 58 who demonstrated that a resin composite conversion rate with water storage rose considerably after one month. The current study may not accurately represent the oral environment because it was an in vitro investigation with a limited sample size.…”
Section: Table 5: Degree Of Conversion Mean Value (%)supporting
confidence: 90%